João Rodrigues's account of sixteenth-century Japan - Rodrigues, João 1558-1633.; Cooper, Michael 1930- (London Hakluyt Society, 2001)
Joao Rodrigues was appointed to compile a history of the Jesuit mission in Japan, 1549-1620. This account describes the country, its peoples, their customs and culture, as well as Chinese astronomy and astrology.
Includes bibliographical references (pages 401-416) and index.
Translation of books 1 and 2 of part 1 of Rodrigues' history.
Keywords: Japan -- Civilization -- To 1600.; Japan -- History -- To 1600.